Women in the sky : gender and labor in the making of modern Korea - Nam, Hwasook, 1959- (ILR Press, an imprint of Cornell University Press, 2021)
"This book examines Korean women factory workers' century-long activism from the 1920s to the present in broad historical context with a focus on gender politics in the labor movement and in the larger society"-- Provided by publisher
Keywords: Women in the labor movement -- Korea -- History -- 20th century.; Women in the labor movement -- Korea (South) -- History -- 20th century.; Women in the labor movement -- Korea (South) -- History -- 21st century.; Manufacturing industries -- Korea -- Employees.; Manufacturing industries -- Korea (South) -- Employees.; Women employees -- Political aspects -- Korea.; Women employees -- Political aspects -- Korea (South); Femmes dans le mouvement ouvrier -- Corée -- Histoire -- 20e siècle.; Femmes dans le mouvement ouvrier -- Corée du Sud -- Histoire -- 20e siècle.; Femmes dans le mouvement ouvrier -- Corée du Sud -- Histoire -- 21e siècle.; Industrie manufacturière -- Corée -- Personnel.; Industrie manufacturière -- Corée du Sud -- Personnel.; Personnel féminin -- Aspect politique -- Corée.; Personnel féminin -- Aspect politique -- Corée du Sud.; HISTORY / Asia / Korea.; Manufacturing industries -- Employees; Women in the labor movement; Korea; Korea (South); 1900-2099; Electronic books.; History